Iogurte probiótico com teor reduzido de lactose adicionado de óleo de linhaça - Becker, Larissa Vargas (2009)
More than 50% of the world population presents conditions of lactase deficiency, in Brazil, 58 million people undergo such genetic disorder. The goal of the present work was to produce probiotic yogurt with reduced contend of lactose added flaxseed oil and to study the viability of lactic and bifid bacteria compared to the flaxseed oil and different contends of lactose. Three out of the seven developed treatments were added with 0,2; 0,5 and 0,8g of lactase enzyme per liter of milk respectively. Microbiological and physic-chemical analysis were carried out in the yogurts. The yogurts with reduced lactose presented a decrease in pH and an increase in the acidity less strong than the other yogurts during twenty-eight days of storage. The contends of lactose found in the yogurts which were added with lactase are considered low, within the patterns and regulations of the for special dietary uses legislation. The ratio found between Streptococcus salivarius ssp. Thermophilus and Lactobacillus delbrueckii ssp. bulgaricus was 2:1, which favors the decrease of postacidification. The number of viable cells of Bifidobacterium sp. and Lactobacillus acidophilus as well as the lactic bacteria stood until the end of the storage period according to the recommendations of the legislation. The fat contends were higher in yogurts added with flaxseed oil and rice flour concomitantly. Only one of the yogurts fit the legislation concerning protein contend, probably due to the substitution of powder milk by the rice flour in the yogurts. Considering the results it is possible to infer that the enzyme lactase used in the experiment efficiently hydrolyzed the lactose of the yogurts and did not compromised the viability of microorganisms of the traditional culture as the probiotic culture.